2004
DOI: 10.1111/j.1365-2141.2004.04956.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion and impaired interferon‐α‐producing capacity of blood plasmacytoid dendritic cells in human T‐cell leukaemia virus type I‐infected individuals

Abstract: Summary Dendritic cells (DCs) play an important role in innate and adaptive immunity. There are two major populations of blood DCs, myeloid DCs (myDCs) and plasmacytoid DCs (pcDCs). pcDCs are particularly important in antiviral as well as in general host defence, as they are the principal producers of type I interferons (IFNs). In this study, we analysed myDCs and pcDCs in healthy controls, human T‐cell leukaemia virus type I (HTLV‐I)‐infected asymptomatic carriers (ACs), and patients with adult T‐cell leukaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
95
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 43 publications
2
95
1
Order By: Relevance
“…The decreased frequency of DCs in ATL patients is consistent with a previous report. 44 We are the first to demonstrate the decreased DC frequency in HAM/TSP patients compared with HDs. Whereas the DC frequency in ATL patients was significantly lower, the expression level of CD1d on mDCs, monocytes, and B cells and that of activation markers (CD86 and HLA-ABC) on circulating DCs was similar among the study groups ( Figure 3, supplemental Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decreased frequency of DCs in ATL patients is consistent with a previous report. 44 We are the first to demonstrate the decreased DC frequency in HAM/TSP patients compared with HDs. Whereas the DC frequency in ATL patients was significantly lower, the expression level of CD1d on mDCs, monocytes, and B cells and that of activation markers (CD86 and HLA-ABC) on circulating DCs was similar among the study groups ( Figure 3, supplemental Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…45 Moreover, the ability of pDCs from ACs to produce type 1 interferon, an important antiviral mechanism of the innate immune system, is impaired. 44 Further studies must address the effect of HTLV-1 infection on DC functions, especially the function to activate iNKT cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, sera obtained from the additional 20 ATL patients were not reactive to SRPK1 protein. It has been reported that T-cell (Kannagi et al, 1991), B-cell (Tanaka et al, 1989) and dendritic cell (Hishizawa et al, 2004b) functions are impaired in HTLV-I-infected individuals. Such immunodeficiency appears to be responsible for the reduced antibody response against SRPK1 in ATL patients despite its high expression, which may limit the usefulness of SRPK1 as a potential target for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the uptake of tumour-cell-derived apoptotic bodies by slanDCs is Dectin-1/CLEC7A-and CD18-independent, and that IFNg-activated slanDCs cultured with fluorescent-labelled, alive HT29 cells contained intracellular apoptotic bodies likely derived from the slanDC-mediated killing of HT29 cells, as previously shown 16 . Circulating mDCs and pDCs from cancer patients are frequently reduced in number and functionally defective [30][31][32][33][34] . Recent works have proved the prognostic significance of the immune response to colon carcinomas (CCR) 35,36 .…”
mentioning
confidence: 99%